PELATIHAN PEMBUATAN KERUPUK UMBI TALAS PADA MASYARAKAT DESA BUHUDAA, KECAMATAN BATUDAA PANTAI, KABUPATEN GORONTALO - Ernikawati, Ernikawati; Badu, Franning Deisi; Puspaningrum, Dian; Abubakar, Siti Khofifah (Universitas Gorontalo, 2026)
The taro cracker-making training is one of the community empowerment efforts in Buhudaa Village, Batudaa Pantai District, Gorontalo Regency, aimed at improving skills and business opportunities based on local potential. Taro (Colocasia esculenta) is a fairly abundant food crop in the region, but its utilization is still limited to household consumption. Therefore, this training activity is designed to provide the community with knowledge and practical skills on how to process taro into a value-added product, namely taro crackers. The methods used include outreach, demonstrations, and hands-on practice so that participants can thoroughly understand the cracker-making process, from raw material selection and dough processing to drying techniques and hygienic packaging. The training results indicated that participants gained a better understanding of local food product diversification and fostered motivation to develop taro-based small businesses. Furthermore, this activity contributed to improving family incomes, strengthening food security, and preserving local wisdom through the utilization of available natural resources. Thus, this training not only impacted individual skills but also encouraged the growth of new entrepreneurs at the village level. Keywords: training, taro crackers, community empowerment, food diversification, Gorontalo